Pengaruh Risk-Based Internal Auditing dan Kompetensi Auditor terhadap Efektivitas Audit Internal: Peran Moderasi Budaya Organisasi - I Putu Laksmana Narayana; I Putu Gede Diatmika; Nyoman Ari Surya Dharmawan (Politeknik Ganesha Medan, 2026)
This study examines the effects of risk-based internal auditing (RBIA) and internal auditor competence on internal audit effectiveness, as well as the moderating role of organizational culture in the public sector. Despite extensive research on internal audit effectiveness in the public sector, prior studies report inconsistent findings regarding the role of technical factors and organizational context, particularly the moderating effect of organizational culture in highly regulated environments. This study adopted a quantitative approach using a survey method with a saturated sampling technique, involving 59 internal supervisory officials at the Regional Inspectorate of Denpasar City. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with an interaction-based moderation model through SmartPLS to examine both direct and moderating relationships among variables. The results revealed that RBIA and internal auditor competence positively and significantly affect internal audit effectiveness. However, organizational culture does not significantly moderate these relationships, indicating that technical and professional factors operate independently of organizational context. This study extends the public sector auditing literature by providing empirical evidence on the limited role of organizational culture as a moderating variable in highly regulated environments and by reinforcing the relevance of stewardship theory in explaining internal audit effectiveness. Practically, the findings suggest that public sector internal audit institutions should prioritize strengthening RBIA implementation and enhancing auditor competence to improve audit effectiveness.